2020
DOI: 10.1007/s42452-020-03930-5
|View full text |Cite
|
Sign up to set email alerts
|

Planar geosynthetic-reinforced soil foundations: a review

Abstract: Geosynthetics-reinforced soil (GRS) foundation can improve the bearing capacity of the foundation and reduce the settlement of the footing, which has been widely applied to the treatment and improvement of soft soil foundation. In recent years, scholars have carried out a large number of studies to reveal the influence of different factors on the load and settlement behaviors of GRS foundations. In this study, the reinforcing mechanisms of reinforced materials are first summarized, and then the literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 96 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…6a, where the indicated terms such as the placement depth of the rst reinforcement layer from the footing base (represented by u), the vertical spacing between the reinforcement layers (represented by h), number of layers of reinforcement (represented by N), and the width of reinforcement (represented by B r ) are the geometrical parameters. The reinforcement materials placed at optimum conditions show the improved higher load-carrying capacity [9][10]. Based on the earlier ndings of Buragadda and Thyagaraj [15], the optimum geometrical parameters of = 0.31, = 0.3, = 4, and = 3.5 have been used in the present study, and these parameters are reported by Buragadda and Thyagaraj [15] corresponding to the same properties of jute geotextile reinforcement as used in the present study.…”
Section: Layout Of Reinforcement Layersmentioning
confidence: 79%
See 1 more Smart Citation
“…6a, where the indicated terms such as the placement depth of the rst reinforcement layer from the footing base (represented by u), the vertical spacing between the reinforcement layers (represented by h), number of layers of reinforcement (represented by N), and the width of reinforcement (represented by B r ) are the geometrical parameters. The reinforcement materials placed at optimum conditions show the improved higher load-carrying capacity [9][10]. Based on the earlier ndings of Buragadda and Thyagaraj [15], the optimum geometrical parameters of = 0.31, = 0.3, = 4, and = 3.5 have been used in the present study, and these parameters are reported by Buragadda and Thyagaraj [15] corresponding to the same properties of jute geotextile reinforcement as used in the present study.…”
Section: Layout Of Reinforcement Layersmentioning
confidence: 79%
“…The load-bearing capacity of the foundation can be signi cantly increased by incorporating the geosynthetic reinforcement layers in different forms such as planar form (i.e., geotextiles, geogrids, and geo-composites), and three-dimensional cellular con nement form (i.e., geocells) into the soil [1][2][3][4][5]. The mobilized tensile resistance of the reinforcement layers during the loading process fundamentally improves the load-carrying capacity of the reinforced soils [6][7][8][9]. In the case of shallow foundations, several researchers have investigated the effect of different types of planar form of reinforcement layers on the soil load-bearing capacity with respect to the settlement of the footing [2-3, 7, 10-23].…”
Section: Introductionmentioning
confidence: 99%
“…Rezultati pokusa su pokazali da je kod različitih gustoća tla najveća nosivost armiranoga tla dobivena u formi inverznog trapezoidnog rasporeda armature, a najmanja nosivost tla kod trapezoidne forme armiranja [18]. Gou i dr. [19] su u radu iznijeli zaključke iz pokusnih istraživanja, kao i zaključke numeričkog i analitičkog modeliranja za mehanizme kod ravninskog armiranja tla za plitko temeljenje. Dobiveni rezultati daju podatke o tomu da se potrebna dubina ugradnje (u) gornjeg sloja armature kreće od 0,3B do 0,4B, gdje je B širina ili promjer temelja.…”
Section: Tablica 1 Prikaz Značajnijih Istraživanja Nosivosti Tla Armi...unclassified
“…Duljina sloja armature (L) varira od 4B do 5B. Numeričkim simulacijama kombiniraju se rezultati dobiveni iz ispitivanja na laboratorijskim modelima s onim dobivenim simulacijama računalnim programima kao što su omjeri opterećenja -slijeganja, porast i raspodjela naprezanja i utjecaj parametara armature, kao što su raspodjela polja pomaka tla, deformacije i raspodjela naprezanja u armaturi te interakcija tla i armature [19].…”
Section: Tablica 1 Prikaz Značajnijih Istraživanja Nosivosti Tla Armi...unclassified
See 1 more Smart Citation